Intellectual property synergies: merging halal certification with Indonesian communal intellectual property rights laws - Disemadi, Hari Sutra; Alhakim, Abdurrakhman; Silviani, Ninne Zahara; Febriyani, Emiliya (Legality : Jurnal Ilmiah Hukum, 2024)
Indonesia possesses significant potential to enhance and expand its halal industry, leveraging its unique cultural assets from many of its indigenous communities. One of the ways to ensure the growth of the halal industry is the facilitation of IPR protection through the legal framework. Using a normative method supported by a statutory approach, this research analyzed the challenges and potentials of integrating halal certification into the communal IPR system in Indonesia. The analysis found many restrictions within the existing positive laws which can prevent the integration of halal certification into the communal IPR system. This research proposed a model of communal IPR according to the challenges identified, along with the normative construction needed to establish it. This model mainly focused on providing normative spaces for the integration of sharia compliance while also making sure that the purposes of IPR protection are fulfilled.